Penyusunan Rencana Aksi Adaptasi Perubahan Iklim Secara Partisipatif - Dhina Mustikaningrum; Suprayitno Suprayitno; Kristiawan Kristiawan (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2025)
Adaptation to climate change by farmers is very urgent to reduce the risk of crop losses. In Tuban Regency, farmers face the problem of flooding which occurs routinely every year and changes in erratic rain patterns increasingly threaten rice production. Farmers need assistance in designing anticipatory steps for environmental changes, especially weather. This community service aims to assist farmers in preparing climate change adaptation action plans. The service partners are farmers who are members of the Bandungrejo Village Water User Farmers Association, Plumpang District, Tuban Regency. The method used is group discussion in a mini field school with a sustainable livelihood assessment (SLA) approach. The results of farmers' analysis of the potential and problems, institutions and capital owned by farmers and farmer organizations show that recurring flood events that occur every year are a priority problem that must be resolved. So farmers hope for collaboration with various parties to handle the Avor River flood which is located in the northern area of Bandungrejo Village. Farmers also plan activities for implementing climate change adaptive technology, extreme weather early warning systems and the need for mitigation through the application of renewable energy installation. Adaptasi perubahan iklim oleh petani sangat diperlukan untuk mengurangi resiko kerugian panen. Di Kabupaten Tuban, petani menghadapi persoalan banjir yang rutin terjadi setiap tahun dan perubahan pola hujan yang tidak menentu semakin mengancam produksi padi. Petani memerlukan pendampingan dalam merancang langkah-langkah antisipasi terhadap perubahan lingkungan, khususnya cuaca. Pengabdian kepada masyarakat ini bertujuan mendampingi petani menyusun rencana aksi adaptasi perubahan iklim. Mitra pengabdian adalah petani anggota Himpunan Petani Pemakai Air Desa Bandungrejo Kecamatan Plumpang Kabupaten Tuban. Metode yang digunakan adalah diskusi kelompok dalam sebuah mini sekolah lapang dengan pendekatan sustainable livelihood assessment (SLA). Hasil analisis petani terhadap potensi dan masalah, kelembagaan dan modal yang dimiliki petani maupun organisasi petani menunjukkan bahwa kejadian banjir yang berulang terjadi setiap tahun adalah persoalan prioritas yang harus dipecahkan. Sehingga petani mengharapkan kolaborasi dengan para pihak untuk penanganan banjir kali avour yang terletak di wilayah utara Desa Bandungrejo. Petani juga merencanakan kegiatan penerapan teknologi adaptif perubahan iklim, sistem peringatan dini cuaca ekstrim hingga kebutuhan akan mitigasi melalui penerapan energi terbarukan.